Anchoring groups for ordered and highly stable monomolecular films on naturally oxidized aluminum: phosphonate versus carboxylate - Cegiełka, Daria; Kozieł, Krzysztof; Zharnikov, Michael; Cyganik, Piotr (Applied surface science, 2024)
Modification of metal oxide surfaces by self-assembled monolayers (SAMs) is attracting growing attention. Carboxylic (CA) and phosphonic (PA) acids are most popular anchoring groups in this context, applied to create hydrophobic coatings, biosensors, and organic field-effect transistors. The efficiency of these devices is crucially affected by the structural quality and stability of the SAM. In this context, we studied the effect of the preparation procedure (solvent, incubation time, and temperature) on the quality of PA SAMs on naturally oxidized aluminum. We demonstrate formation of PA SAMs matching structural quality of archetypical alkanethiols on gold. Next, we compare their stability with analogous CA SAMs. Our data show that PA SAMs not only exhibit much higher hydrolytic stability but are also capable to protect aluminum substrate from oxidation and degradation. Importantly, even small improvement of the PA SAMs quality, translates into enormous increase of their hydrolytic stability crucial for majority of applications. Finally, we demonstrate that the thermal stability of PA on oxidized aluminum is by ∼250 K higher than CA SAMs, and by ∼200 K higher than for thiols on gold, which makes PA SAMs an excellent candidate for organic electronics, where overheating problems and high-temperature fabrication procedures are common issues.